The role of mining-induced seismicity amplitude and frequency in gob-side roadway rib spalling - Zong-long Mu; Jiaxin Zhuang; Xiufeng Zhang; Jinglong Cao; Zujun Lu; Xingen Ma; Fuhong Li (Energy Exploration & Exploitation)
During underground coal mining, Mining-induced seismicity is a crucial factor leading to roadway deformation. Based on a case study of rib spalling caused by mining-induced seismicity in China, this paper utilizes the Universal Distinct Element Code to investigate the mechanism of rib spalling. It analyzes the stress evolution process of roadway surrounding rock and the damage process under the influence of mining-induced seismicity. Additionally, it examines the relationship between seismic wave amplitude, frequency and the damage characteristics of roadway surrounding rock. Findings show that seismic waves induce stress concentration zones in the deeper surrounding rock, causing shear failure, while stress concentration zones emerge in the top, bottom and shoulders of roadway, leading to tensile failure in the shallower surrounding rock. With increasing seismic wave amplitude, the critical crack length of surrounding rock decreases, resulting in a linear increase in crack count and distribution area. The roadway exhibits a ‘ n '-shaped damage profile primarily driven by shear failure. With increasing seismic wave frequency, the crack count in the surrounding rock of the roadway exhibits a trend of initially increasing and then decreasing. This trend becomes more pronounced with larger amplitudes. Rib spalling damage is influenced by seismic wave frequency and amplitude: frequencies of 20–25 Hz and 80–100 Hz require amplitudes exceeding 3 m for damage, while 25–30 Hz and 55–80 Hz require amplitudes over 2 m, and 30–55 Hz necessitate amplitudes exceeding 1.5 m.